Adult overweight and obesity prevalence by two anthropometric criteria - Ronaldo Domingues Filardo; Edio Luiz Petroski (Desafio Singular, 2007)
To determine and compare overweight and obesity by two anthropometric criteria, BMI and %Fat, of adults aged 20 to 40 years old. Data were collected from 400 subjects enrolled on distinct exercise training programs in Curitiba, Paraná. Subjects were organized in 4 age groups from age 20 to 40 years old. BMI and %Fat overweight and obesity criteria were those of WHO (2000) and Lohman (1992), respectively. For such, weight, stature and fours skin folds (triceps, subescapula, iliac crest and medial calf) data were collected. The excess of body weight prevalence was significantly higher (p<0.05) for %Fat (66.2%) than for BMI (45.6%) of which 53.2% were overweight and 13% obese. For BMI, the prevalence of overweight and obesity were, respectively, 36.3% and 9.3%. Accordingly to the %Fat diagnostic, a subject between ages 35-39 years old has a 300% and 45% chance of being classified as obese and overweight, respectively, than a subject aged from 20-24 years old. Likewise, for BMI, a subject has a 46% chance of being classified as overweight at the age 30-34 years old than a subject between ages 20-24 years old. This study found a prevalence of excess body weight for one out of three at the moment of enrollment. The risk of obesity, as excess of body weight, can better be identified by %F than BMI.